Analisis Disiplin, Iklim Kerja Dan Kompensasi Dalam Meningkatkan Kinerja Pendidik - Suci Kurniasih; Sony SM Laksono (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Discipline, Work Climate, and Compensation have an important role in improving teacher performance. This research was conducted to particularize how much influence of the discipline, work climate and compensation to the performance of the teachers. This research uses a quantitative research method where the data in this study will be processed and the results in the form of figures and analysis. Population and sample of this research were all teachers at SMKN 1 Semen, amounting to 55 respondents. The analysis that used in this research is multiple linear regression analysis, with the research instrument test, classic assumption test, F test and T test. The statistical calculations is aided SPSS 21 for Windows. So, the result of this research is to conceive any partial effect that disciplines, work climate, and compensation can predispose teacher performance at SMKN 1 Semen simultaneously.